Dangerous Pollutants (Xenobiotics) in Urban Water Cycle - Hlavinek, Petr.; Hlavinek, Petr.; Bonacci, Ongjen.; Bonacci, Ongjen.; Marsalek, Jiri.; Marsalek, Jiri.; Mahrikova, Ivana.; Mahrikova, Ivana. (NATO Science for Peace and Security Series C: Environmental Security, 2008)
Growing population and rising standards of living exert stress on water supply and the quality of drinking water. Some of these pressures can be reduced by demand management and water and wastewater reuse. In wastewater ma- gement, new challenges are caused by new chemicals of concern, including endocrine disrupters, pharmaceuticals, hormones, and personal care products, which often pass through wastewater treatment plants unabated, but may cause serious impacts on receiving aquatic ecosystems. The topics focused on evaluation of impact of xenobiotics in the whole Urban Water Cycle are an interdisciplinary task which has a rising concern these days. Xenobiotics includes both inorganic elements like heavy metals, metalloids and man-made organic compounds such as pesticides, surfactants, solvents, fragrances, flavours, and pharmaceuticals as well as endocrine dis- pters. It has been estimated that 70,000 xenobiotics may potentially be hazardous for humans and/or ecosystems. Water supply, urban drainage and wastewater treatment systems were originally designed to solve just conventional problems such as supply of potable water, flooding prevention and sanitation. The main problem within the conventional urban water cycle approaches is absence of design to deal with xenobiotics. Nowadays can be seen increased focus on rainwater use, wastewater reclamation and reuse in industrial and as well in domestic sector what increase the exposure to xenobiotics.